Thyroid Function, Diabetes, and Common Age-Related Eye Diseases: A Mendelian Randomization Study - Ellervik, Christina; Boulakh, Lena; Teumer, Alexander; Marouli, Eirini; Kuś, Aleksander; Buch Hesgaard, Helena; Heegaard, Steffen; Blankers, Lizette; Sterenborg, Rosalie; Åsvold, Bjørn Olav; Winkler, Thomas Wolfgang; Medici, Marco; et al. (Thyroid (New York, N.Y.), 2024)
Previous Mendelian randomization (MR) studies showed an association between hypothyroidism and cataract and between high-normal free thyroxine (FT4) and late age-related macular degeneration (AMD), but not between FT4, thyroid stimulating hormone (TSH), or hyperthyroidism and diabetic retinopathy or cataract. These studies included a limited number of genetic variants for thyroid function and did not investigate autoimmune thyroid disease (AITD) or glaucoma, include bidirectional and multivariable MR (MVMR), and examine sex differences or potential mediation effects of diabetes. We aimed to address this knowledge gap. We examined the causality and directionality of the associations of AITD, and FT4 and TSH within the reference range with common age-related eye diseases (diabetic retinopathy, cataract, early and late AMD, and primary open-angle glaucoma). We conducted a bidirectional two-sample MR study utilizing publicly available genome-wide association study (GWAS) summary statistics from international consortia (ThyroidOmics, International AMD Genetics Consortium, deCODE, UK Biobank, FinnGen, and DIAGRAM). Bidirectional MR tested directionality, whereas MVMR estimated independent causal effects. Furthermore, we investigated type 1 diabetes (T1D) and type 2 diabetes (T2D) as potential mediators. Genetic predisposition to AITD was associated with increased risk of diabetic retinopathy ( = 3 × 10 ), cataract ( = 3 × 10 ), and T1D ( = 1 × 10 ), but less likely T2D ( = 0.01). MVMR showed attenuated estimates for diabetic retinopathy and cataract when adjusting for T1D, but not T2D. We found pairwise bidirectional associations between AITD, T1D, and diabetic retinopathy. Genetic predisposition to both T1D and T2D increased the risk of diabetic retinopathy and cataract ( < 4 × 10 ). Moreover, genetically predicted higher FT4 within the reference range was associated with an increased risk of late AMD ( = 0.01), particularly in women ( = 7 × 10 ). However, we neither found any association between FT4 and early AMD nor between TSH and early and late AMD. No other associations were observed. Genetic predisposition to AITD is associated with risk of diabetic retinopathy and cataract, mostly mediated through increased T1D risk. Reciprocal associations between AITD, diabetic retinopathy, and T1D imply a shared autoimmune origin. The role of FT4 in AMD and potential sex discrepancies needs further investigation.